Analysis forecasting sales of tart products - Dewi Cahyani Pangestuti; Raulian Franciskus Pasaribu (Faculty of Economics and Business Mulawarman University, 2021)
Sales forecasting is an effective and efficient tool for organizations or business people to predict the products that will be produced. Sales forecasting is a method that uses historical data as a reference to get a picture of future value. This research was conducted at the Kuwenak Shop, which produces in the food sector, to be precise, cakes or birthday cakes. On the occasion of this research, there are three forecasting methods used, including moving average, exponential smoothing, and linear trend, taking into account the smallest error rate or error in each method. The linear trend forecasting method is the best choice because it has a low error rate. Specifically, the MAD error value is 2.4, the MSE error is 6.6, the MAPE error is 5.9% and the standard error is 9.3. From the data management on the selected method, the linear trend sales forecasting method for cake products predicts that for the next week, Kuwenak Shop s can produce 40.6 or 41 products. This means that Kuwenak Shop can provide 41 tarts the following week or even each week.